INTERRELATION OF CONCEPTUAL CATEGORIES “STOCKS”, “COSTS” AND “EXPENSES” AND SEQUENCE OF PRESENTING THEM IN THE FINANCIAL REPORTING - O. A. Ageeva (Вестник университета)
The article is devoted to the study of three conceptual categories of accounting: stocks, costs and expenses, in their interrelation defined by the sequence in which they are presented in financial reporting in accordance with three stages of the capital cycle: procurement – production - sales. The problem caused by mixing up the information about the categories under study while presenting them in the financial reporting has been formulated. In particular, the complex item «inventory» includes both raw materials, materials, goods related to the procurement stage, and work-in-progress with finished products formed at the production stage. In order to overcome this problem, an assessment of the existing methodology for reflecting information about the concepts under study in financial statements has been given, and the need and directions for its improvement have been justified.